Dinamika Komunikasi Dalam Pembinaan Tahfiz Al-Qur’an: Perspektif Dari Pesantren Tahfidz Al-Qur’an Al Manshuriyah Deli Serdang - Subuhan Subuhan; Hotni Sari Harahap; Ade Rahman Matondang (Journal of Innovative and Creativity, 2025)
This study aims to explore the dynamics of communication between instructors and students in the process of Qur’an memorization (tahfidz) at the Tahfidz Al-Qur’an Al Manshuriyah Islamic Boarding School in Deli Serdang. A descriptive qualitative approach was employed, using interviews, observations, and documentation as data collection techniques. The informants included the foundation’s leader, instructors (ustadz/ustadzah), and students. The findings reveal that the communication patterns applied by the instructors are varied and personalized, incorporating verbal and non-verbal communication along with emotional approaches. Teachers combined motivational and corrective communication with a balance of firmness and gentleness to maintain students’ enthusiasm and comfort in memorization. Factors such as emotional condition, motivation, communication style, and the pesantren’s environment influenced the effectiveness of communication. The study also identified several communication challenges, including students’ fear or shyness, differing backgrounds, and fluctuating motivation—overcome through personalized, empathetic approaches and positive reinforcement. In conclusion, strong interpersonal communication between instructors and students plays a pivotal role in the success of tahfidz development and the formation of resilient student character.